Grass weed ecology and control of atrazine-resistant Palmer amaranth (Amaranthus palmeri) in grain sorghum (Sorghum bicolor) - Albers, Jeffrey J. (Kansas State University, 2018)
An opportunity for postemergence (POST) grass weed control has recently been approved with ALS-resistant grain sorghum, however, grass weed emergence timing and crop tolerance to grass competition are not well understood. To address the importance of POST application timing, a critical period of weed control (CPWC) for grass competition in grain sorghum was developed. Field experiments were established near Manhattan and Hays, KS in 2016 and 2017, and near Hutchinson, KS in 2017 to determine the CPWC. Each site provided a different grass species community. A total of ten treatments were included, with four treatments maintained weed-free until 2, 3, 5, or 7 weeks after crop emergence, four treatments receiving no weed control until 2, 3, 5, or 7 weeks after crop emergence, and two treatments were maintained weed-free or weedy all season. Treatments did not influence grain yield at Hutchinson because of a lack of season-long weed emergence. At Hays the CPWC began at crop emergence and ended 28 days later. At Manhattan the CPWC began 27 days after emergence and continued through grain harvest. The CPWC in grain sorghum depends on rainfall and competitive ability of the weed species. The start of the CPWC began when weeds emerged, thus a POST application should be targeted 14 to 21 days after emergence of grain sorghum. Emergence and development of large crabgrass, barnyardgrass, shattercane, and giant, green, and yellow foxtails were studied near Manhattan, KS after seeding on April 11, 2017. Barnyardgrass had the longest duration of emergence, beginning at 180 GDD after seeding and continuing through July. Large crabgrass had the shortest duration of emergence from 325 to 630 GDD after seeding. In general, all grasses began to emerge in late April and most species completed 90% emergence by early June. Grain sorghum is typically planted at this time, so grass weed control prior to planting is critical. Palmer amaranth is a troublesome weed in double-crop grain sorghum production fields in Kansas. The presence of herbicide-resistant populations limits options for weed management. Field experiments were conducted to evaluate 14 different herbicide programs for the management of atrazine-resistant Palmer amaranth in double-crop grain sorghum at Manhattan and Hutchinson, KS in 2016 and 2017. Programs included eight PRE only and six PRE followed by POST treatments. Programs that had very long chain fatty acid-inhibiting herbicides provided greater control of atrazine-resistant Palmer amaranth by three weeks after planting sorghum. Programs of PRE followed by POST provided greater control of both atrazine-resistant and -susceptible Palmer amaranth by eight WAP compared to PRE alone. These results illustrate the value of residual herbicides, as well as an effective postemergence application, in double-crop grain sorghum. Early season grass and Palmer amaranth control with the use of residual herbicides such as very long chain fatty acid-inhibitors provide a competitive advantage to grain sorghum. Utilizing weed emergence patterns to time effective POST applications, in unison with residual herbicides, will provide season-long weed control in Kansas grain sorghum fields.
Keywords: Weed emergence; Double-crop; Critical period; Grain sorghumAtrazine-resistance